2004
DOI: 10.1002/bdm.471
|View full text |Cite
|
Sign up to set email alerts
|

What is learned from experience in a probabilistic environment?

Abstract: Three experiments explored what is learned from experience in a probabilistic environment. The task was a simulated medical decision-making task with each patient having one of two test results and one of two diseases. The test result was highly predictive of the disease for all participants. The base rate of the test result was varied between participants to produce different inverse conditional probabilities of the test result given the disease across conditions. Participants trained using feedback to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For example, when considering the probability that a patient has colorectal cancer after receiving a negative FOBT test, a physician could think back to a set of similar patients (who have a similar pretest likelihood or a similar set of demographic characteristics and symptoms) and who received a negative FOBT test, and estimate the percentage of these patients who eventually were found to have colorectal cancer. This process is believed to be the process participants use when they have access to extensive prior Bnatural^experience (Kleiter, 1994) or even lab-based trial-by-trial learning experience (Edgell et al, 2004; see also Barbey & Sloman, 2007;Gigerenzer & Hoffrage, 1995;Kleiter et al, 1997). Noisy recall of these quantities could also contribute to the imperfect coherence between the pretest, likelihood, and posttest judgments (Hilbert, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when considering the probability that a patient has colorectal cancer after receiving a negative FOBT test, a physician could think back to a set of similar patients (who have a similar pretest likelihood or a similar set of demographic characteristics and symptoms) and who received a negative FOBT test, and estimate the percentage of these patients who eventually were found to have colorectal cancer. This process is believed to be the process participants use when they have access to extensive prior Bnatural^experience (Kleiter, 1994) or even lab-based trial-by-trial learning experience (Edgell et al, 2004; see also Barbey & Sloman, 2007;Gigerenzer & Hoffrage, 1995;Kleiter et al, 1997). Noisy recall of these quantities could also contribute to the imperfect coherence between the pretest, likelihood, and posttest judgments (Hilbert, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work has found that a number of factors can lead to improved Bayesian reasoning (Gigerenzer & Hoffrage, 1995;Krynski & Tenenbaum, 2007). In particular, one setting that can lead to improved posterior probability judgments is when individuals experience the contingency between the two variables in question (e.g., mammogram result and having cancer) in a trial-by-trial learning paradigm (ChristensenSzalanski & Beach, 1982;Edgell, Harbison, Neace, Nahinsky, & Lajoie, 2004).…”
Section: Abstract Bayesian Reasoning Probabilistic Reasoning Diagmentioning
confidence: 99%
“…Paradoxically, participants in their experiments never actually experienced data sequentially, that is, “as a series of events.” Instead, they observed totals. That is, Gigerenzer and his colleagues presented data in the form of summarized natural frequencies (see also Edgell, Harbison, Neace, Nahinsky, & Lajoie, 2004, p. 214).…”
Section: Frequency Data and Probabilistic Reasoningmentioning
confidence: 99%
“…[11][12][13][14] The broader community of medical decision making researchers has not embraced the topic of heuristics and biases approach with sustained enthusiasm. Although some errors attributable to previously identified heuristic strategies have been demonstrated with medical vignettes 15 as well as simulated medical decision-making tasks, 16 others have failed to replicate those errors. 17 There has been an unsteady stream of demonstrations of inaccuracies of physician judgments of probability about their own patients or hypothetical ones, influenced by recency, 18 by the utility of the outcome, 19 or by anchoring on one's original judgments.…”
Section: My Heuristics Your Heuristicsmentioning
confidence: 99%